Pengaruh Gaya Kepemimpinan, Disiplin Kerja Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Mas Silueta Semarang - Ema Setyaningrum; Darsono Darsono (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2022)
This research is motivated by the achievement of work targets for employees of PT. MAS Silueta Indonesia Semarang which has not been maximized. This study aims to analyze leadership style (X1), work discipline (X2), and work environment (X3) on employee performance (Y) in the Office of Supervision and Service of Customs and Excise Middle Type Tanjung Emas Customs. The analytical method in this study is Multiple Linear Regression. Samples were taken using saturated sampling techniques, namely a number of 130 respondents. The results showed that leadership style has a positive effect on the performance of employees at PT. MAS Silhouette Semarang. Work discipline has a positive effect on the performance of employees of PT. MAS Silhouette Semarang. The work environment has a positive effect on the performance of employees of PT. MAS Silhouette Semarang. Based on the results of the research, suggestions can be given to improve the work leadership style at PT. MAS Silueta Semarang by frequently providing stimulus in the form of bonuses for those who excel and awards or promotions. Improving employee work discipline by evaluating employee discipline periodically. Give rewards to disciplined employees and threaten those who are not disciplined Improve the quality of the work environment because based on research the work environment does not affect employee performance. If the quality of the work environment has been improved, it is likely that employee performance will also increase.